Isolation of Methyl Laurate from Coconut Oil as Raw Material for Fatty Alcohol Sulfate - Arbianti, Rita; Utami, Tania Surya; Nugroho, Astri (Makara Journal of Technology, 2008)
Isolation of Methyl Laurate from Coconut Oil as Raw Material for Fatty Alcohol Sulfate. Methyl laurate is a raw or base material for many industries, including surfactant industries. In this research, coconut oil (VCO) is transesterified with methanol to produce methyl ester, using NaOH as the catalyst. Methyl laurate is then separated by method based on the difference in melting point. This research focuses at determining the effects of some variables in transesterification on the concentration of produced methyl laurate. The variables are temperature (40 oC, 50 oC, 60 oC, 80 oC), time of transesterification reaction (0,5 hour, 1 hour, 1,5 hours, 2 hours, 3 hours), and the percent weight of the catalyst NaOH (0,5 %, 1 %, 1,5 %, 2 %, 3 %). Research showed the concentration of methyl laurate increased, following the increased temperature, time, and percent weight of catalysts. Optimal conditions were acquired at reaction temperature of 60oC, reaction time of 2 hours, and percent weight of the catalyst NaOH of 2 %. Laurate acid conversion to methyl laurate that yielded from optimal conditions, after the separation based on melting point, was 55,61 %.